Respuesta :
Answer:
(-2, 0)
Step-by-step explanation:
Use elimination: add the two systems. Because the left is equal to right, you are adding the same thing and it's legal.
-x+3y=2
+ (x+y=-2)
Add each term
-x+x + 3y+y = 2+ -2
4y=0
y=0
x+y=-2
x+0=-2
x=-2
Answer:
x=-2, y=0
Step-by-step explanation:
-x+3y=2
X+y=-2
We can add these two equations together to eliminate x
-x+3y=2
x+y=-2
--------------
4y = 0
Divide each side by 4
4y/4 = 0/4
y=0
Now we still need to find x
x+y = -2
Substitute x=0
0+y = -2
y= -2